Admixture Increases Genetic Diversity and Adaptive Potential in Australasian Killer Whales - Reeves IM; Totterdell JA; Sandoval-Castillo J; Betty EL; Stockin KA; Oliphant Stewart R; Johnstone M; Foote AD (John Wiley and Sons Ltd, 2025)
Admixture is the exchange of genetic variation between differentiated demes, resulting in ancestry within a population coalescing in multiple ancestral source populations. Low-latitude killer whales (Orcinus orca) populations typically have higher genetic diversity than those in more densely populated, high productivity and high-latitude regions. This has been hypothesized to be due to episodic admixture between populations with distinct genetic backgrounds. We test this hypothesis by estimating variation in local ancestry of whole genome sequences from three genetically differentiated, low-latitude killer whale populations and comparing them to global genetic variation. We find 'Antarctic-like' ancestry tracts in the genomes of southwestern Australia (SWA) population including recent (within the last 2-4 generations) admixture. Admixed individuals had, on average, shorter and fewer runs of homozygosity than unadmixed individuals and increased effective population size (Ne). Thus, connectivity between demes results in the maintenance of Ne of relatively small demes at a level comparable to the sum of Ne across demes. A subset of the admixed regions was inferred to be evolving under selection in the SWA population, suggesting that this admixed variation may be contributing to the population's adaptive potential. This study provides important and rare empirical evidence that small populations can maintain genetic diversity due to sporadic admixture between different genetic backgrounds and that admixed ancestry can promote the long-term stability of Ne.
Keywords: cetacean; effective population size; heterosis; inbreeding; introgression